Politik Hukum Pembentukan UU Paten di Indonesia: Industrialisasi, Liberalisasi, dan Harmonisasi - M. Zulfa Aulia (Fakultas Hukum Universitas Islam Indonesia, 2015)
Patent protection in Indonesia still leaves various problems, both in terms of practical level (implementation) and conceptual level (public acceptance). This study aims to investigate the problematic patent protection from the point of governing law, in this case it is due to the reasons underlying its formation. This is a normative research with a political approach. The legal materials used in the form of the treatise of the trial establishment of patent law, Law No. 6 In 1989, Law No. 13 of 1997 and Law No. 14 of 2001 on Patents. Secondary legal materials in the form of articles that accompany or responded to the formation of the law, and the materials that explain the situation when the law was formed. It comes up with a conclusion that the establishment of the Patent Act is originally intended to encourage industrialization in the country, but in fact is more highly affected by the desire to keep abreast of political and international trade, especially that of developed countries, more adjusted to the substance of the Act by the International Agreement (TRIPs), and create better (foreign) investment climate. The assimilation of domestic-foreign interest more or less would affect the acceptance and implementation of patent protection leading to stumbling blocks as seen today.